(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Physical fitness needs to be possessed by every athlete according to their sport to improve their performance. Muscular endurance is one of the components that support physical fitness. The purpose of this study was to determine the relationship between energy and protein intake, nutritional status, hydration status, body fat percentage, and muscle mass to the muscular endurance of competing category pencak silat athletes at the DKI Jakarta Student Sports Training Center. This study used a cross-sectional research model design with a sample size of 12 people. The sample was taken using the total sampling technique. The statistical analysis used to see the relationship between variables was the Pearson test and the Spearman rank test. The results showed that there was no relationship between energy intake (p=0.113) and protein (p=0.310), nutritional status (p=0.736), hydration status (p=0.232), body fat percentage (p=0.153) and muscle mass (p=0.095) to the muscular endurance of competing category pencak silat athletes at the DKI Jakarta Student Sports Training Center. The results showed that there was no significant relationship between energy and protein intake, nutritional status, hydration status, body fat percentage, and muscle mass on the muscular endurance of sparring category martial arts athletes. Nevertheless, efforts to increase muscle endurance still need to be done through the fulfillment of appropriate nutritional intake, monitoring body composition, consistent training, and maintaining good hydration.